The modeling of LED's disposition - Jurgita Dabulytė; Feliksas Ivanauskas; Artūras Žukauskas (Lietuvos Matematikos Rinkinys)
The goal of this work is to construct the scheme of constructing light  – emitting diodes system. The mathematical model was written for a light-emitting diodes lamp. The finite difference technique was used for the discretization of mathematical model.